(untitled) (Issues in Social and Environmental Accounting (ISEA), 2014)
In recent years, the hotel industry has recognized the need to have more environmentally friendly operations. The main focus, however, has been on improving environmental manage ment practices in developed countries. Furthermore, most attempts to develop assessment tools for green practices have come from such countries as well, which have a different socio economic situation from developing countries. Therefore, to capture a more accurate picture of environmental management practices from the developing country context, specifically a Ma laysian context, the authors in this paper created an index to measure the level of green prac tices among Malaysian hotels. Doing so, however, resulted in a search for green index develop ment methods. This lead to the discovery that existing tools such as the Delphi method were not appropriate tools that could be used to develop a Malaysian green index. To address the above, the authors propose a green index development method that can be used for a Malaysian and developing country context. Hence, in this paper, the method of developing a green prac tice index for the Malaysian hospitality industry, the differences and advantages of this method compared to the commonly used Delphi method and finally the Malaysian Green Practice In dex for the hotel industry are presented.